Pengaruh Kualitas Pelayanan Dan Promosi terhadap Kepuasan Konsumen - Mulyani, Rema; Ahmad Gunawan H. (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2022)
The objectives to be achieved by the authors in this study are: to determine the effect of the influence of service quality and promotion on consumer satisfaction for Tunas Honda Motor Dealer Sukabumi. This research method belongs to the type of quantitative research with associative causality research. Associative research is a research problem formulation that is asking the relationship between two or more variables. Quantitative research method is a research method based on the philosophy of positivism, used to research on a particular population or sample. The data was processed using the SPSS version 26 program. Quantitative analysis includes validity and reliability testing, prerequisite analysis test, coefficient of determination analysis test (R2) and hypothesis testing including t test and f test. The data analysis technique used is multiple linear regression analysis as follows: Y = 13.565 + 0.169X1 + 0.557X2 The results of multiple linear regression analysis, from the coefficient value (b1) -0.169, this means that every time there is an increase in service quality, customer satisfaction has increased. While the promotion shows that the coefficient value (b2) is 0.557, this means that every time there is an increase in promotion, consumer satisfaction also increases. The t-test shows that the X1 variable has a significant level of 0.026 <0.05 and the t-count value is 2.271 > t-table 1.988, so H1 is accepted. The X2 variable has a significant value of 0.000 <0.05 and the t-count value is 6.541> t-table 1.988, then H2 is accepted. Together or there is a simultaneous relationship between service quality and promotion of customer satisfaction, seen from the calculated F value of 62.720 > F table 3.10 and significant F value 0.000 < 0.05 probability value. So there is a positive and significant influence between service quality and promotion simultaneously on customer satisfaction at the Tunas Honda Sukabumi Motor Dealer. The result of the Adjusted R square number is 0.587 or 58.7%, which means that the variable quality of service and promotion has an effect of 58.7% and the rest is influenced by other variables by 41,3%.